Early effects of irradiation on laryngeal mucosa in a gastroesophageal reflux model: an experimental study - ATASOY, BESTE MELEK; ÖZBEYLİ, DİLEK (SPRINGER, 2018)
The aim of this study was to evaluate the early histopathological changes of gastroesophageal reflux and irradiation on laryngeal mucosa in rats. Animal study. Experimental animal laboratory, tertiary referral center. Twenty-four adult female Wistar Albino rats were grouped as: control (n = 6), reflux and irradiation (n = 10), and irradiation (n = 8). Rats were operated to create a reflux model 30 days before irradiation. Ionizing radiation was administered in a single fraction of a 20 Gy to the larynx. Laryngeal tissue samples were taken at the 4th day of irradiation and all specimens underwent histopathological examination. Edema and vascular dilation in lamina propria were higher in the reflux and irradiation, and irradiation groups than control group. Inflammation was higher in the reflux and irradiation group than the control group. Inflammation in squamous epithelium was higher in the reflux and irradiation and irradiation groups compared to the control group. Inflammation in the squamous epithelium of the irradiation group was higher than the reflux and irradiation group. In the respiratory tract epithelium, inflammation was higher in the reflux and irradiation group; additionally, a significant loss of cilia was present in the reflux and irradiation and irradiation groups while pseudostratification was higher in the reflux and irradiation group. Ionizing radiation-induced inflammation may increase on previously inflammated area due to gastroesophageal reflux. Therefore, it may be helpful to investigate and treat the reflux in laryngeal cancer patients that will receive ionizing radiation.
Keywords: Gastroesophageal reflux; Inflammation; Larynx; Ionizing radiation; Animal study; LARYNGITIS; SYMPTOMS; INJURY; RATS